2004
DOI: 10.1074/jbc.m407700200
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Endogenous Akt/IAPs and MEK1/ERK Pathways in Counteracting Endoplasmic Reticulum Stress-induced Cell Death

Abstract: Endoplasmic reticulum (ER) stress has been implicated in the pathogenesis of many diseases and in cancer therapy. Although the unfolded protein response is known to alleviate ER stress by reducing the accumulation of misfolded proteins, the exact survival elements and their downstream signaling pathways that directly counteract ER stress-stimulated apoptotic signaling remain elusive. Here, we have shown that endogenous Akt and ERK are rapidly activated and act as downstream effectors of phosphatidylinositol 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
247
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(270 citation statements)
references
References 64 publications
(61 reference statements)
19
247
1
2
Order By: Relevance
“…As previously published [43,46] , short-term (from 0 to 4 h) ER stress stimulation could increase AKT activity, while long-term (from 8 to 12 h) stimulation could suppress AKT activity. This reflects the dual character of ER stress: the adaptive/moderate level stress (featured by increased chaperone proteins and decreased misfolded proteins) and the destructive/excessive level stress (featured by activating JNK, apoptosis signal-regulating kinase (ASK)) [2,3,30,47] .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…As previously published [43,46] , short-term (from 0 to 4 h) ER stress stimulation could increase AKT activity, while long-term (from 8 to 12 h) stimulation could suppress AKT activity. This reflects the dual character of ER stress: the adaptive/moderate level stress (featured by increased chaperone proteins and decreased misfolded proteins) and the destructive/excessive level stress (featured by activating JNK, apoptosis signal-regulating kinase (ASK)) [2,3,30,47] .…”
Section: Discussionsupporting
confidence: 54%
“…Several diabetes-inducing agents have also been demonstrated as causing insulin resistance in a MEK-dependent manner [35,20] . ER stress was also reported to induce activation of ERK [46] , and ATF6 was shown to counteract the effects of ER stress [23,24] . Based on this prior evidence and our results (Figures 4 and 5), it could be concluded that excessive ER stress could increase the basal, but decrease the insulin-induced, activity of ERK.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation/activation of Akt results in upregulation of the glucose transporter GLUT1 and promotes the translocation of hexokinase into the mitochondria (45). It has also been reported that in addition to UPR, ER stress activates parallel endogenous cell survival mechanisms that directly buffer apoptotic signals through the Akt and ERK pathways (29) and via the antiapoptotic proteins cIAP-2 and XIAP (46). We show that the inhibition of Akt in 2-DGtreated ALL cells results in synergistic cell death.…”
Section: Discussionmentioning
confidence: 74%
“…In addition to PERK, phosphorylated Akt can activate Nrf2 and thereby participate in the ER stress-associated prosurvival response. 34 Prolonged ER stress has been shown to suppress phosphorylation of Akt and thereby promote apoptosis. 35 Consistent with these findings, phosphorylated Akt abundance was markedly reduced in the kidneys of our untreated Imai rats.…”
Section: Discussionmentioning
confidence: 99%